The Emerald handbook of challenge based learning - Vilalta-Perdomo, Eliseo; Hernández, Jorge Membrillo; Villarreal, Rosario Michel; Lakshmi, Geeta; Martínez-Acosta, Mariajulia (Emerald Publishing Limited, 2022)
Challenge-Based Learning (CBL) is a cutting-edge educational approach that integrates traditional learning modules (theory and practice) with real-life challenges that require innovative solutions and that can be applied to a variety of subjects. As the first landmark work on this innovative methodology, The Emerald Handbook of Challenge Based Learning offers an in-depth exploration on how to conceive, design, implement, monitor, and develop CBL initiatives in Higher Education Institutions. International experts explore the use of CBL in different disciplines at university level, and present findings from its implementation based on students' first-hand experiences. They provide real examples on how to implement CBL in different disciplines and formats, from face to face to blended deliveries. Crucially, they offer ways to implement CBL effectively in disciplines less connected to CBL practice, such accounting, finance, marketing and sustainability, food technology, biomedicine, and ICT to name a few. Results, from the implementations reported, suggest that CBL increases students' understandings of real-life settings and is conducive to students' development of 21st century skills. Given the shift in education towards finding solutions to real life challenges, particularly in the wake of the coronavirus pandemic, this novel handbook will be crucial reading for researchers, course designers, and teachers across a range of subject areas, and those interested in improving teaching methods, and adopting new teaching styles, across higher education.